Product market regulation and macroeconomic performance: a review of cross country evidence - Fabio Schiantarelli (Institute for the Study of Labor (IZA), 2005)
The main purpose of this paper is to provide a critical overview of the recent empirical contributions that use cross country data to study the effect of product market regulation and reform on a country's macroeconomic performance. After a brief review of the theoretical literature and of relevant micro-econometric evidence, the paper discusses the main data and methodological issues related to empirical work on this topic. It then critically evaluates the cross country evidence on the effect of product market regulation on mark-ups, firm dynamics, investment, employment, innovation productivity, and output growth. A summary of what we learn from the econometric results concludes the paper.
Keywords: D24; K20; L10; L51; O31; O40; O57; 330; regulation; product market; performance; productivity; innovation; growth; Regulierung; Produktivität; Mikroökonometrie